RAYAP KAYU (ISOPTERA) PADA RUMAH-RUMAH ADAT MINANGKABAU DI SUMATERA BARAT - Ningsih, Deffi Surya; Julia, Za’aziza Ridha; Hilmi, Larissa; Darmi, Leo (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Minangkabau traditional houses in West Sumatra has a high historical value, but it has the serious damage caused by termite infestation. The purpose of this researchÂ was to determine the types of termites that attack Minangkabau traditional houses in West Sumatra, Research the wood termites (Isoptera) in Minangkabau traditional houses in West Sumatra have been conducted in March and July 2013. Direct sampling methods used for collecting termites on mikrosite. Three species of termites were foundÂ that belong to two subfamilies, those Â are Macrotermes gilvus Hagen, Macrotermes sp. (Macrotermitinae) and Nasutitermes matangensis Haviland (Nasutitermitinae).Â Keywords: Isoptera, Termitidae, Minangkabau traditional houses, Macrotermitinae, Nasutitermitinae.